2012
DOI: 10.1111/j.1365-2214.2012.01400.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychological adjustment among left‐behind children in rural China: the role of parental migration and parent–child communication

Abstract: Background Left-behind children refer to those rural children who are under 18 years of age and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
158
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(166 citation statements)
references
References 9 publications
7
158
1
Order By: Relevance
“…Ye and Pan also suggested that abnormal and sometimes bizarre behavior was common among LBC as a means of attracting their parents' or caregivers' attention and suppressing their loneliness. Su, Li, Lin, Xu, and Zhu (2013) compared LBC with one migrating parent, LBC with two migrating parents, and non-LBC, and found that both groups of LBC experienced a higher degree of loneliness than did non-LBC. In addition, Gao et al (2010) found that, compared to non-LBC, a higher percentage of LBC reported feeling sad or hopeless and had ideations of suicide or leaving home.…”
Section: Emotional and Behavior Problemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ye and Pan also suggested that abnormal and sometimes bizarre behavior was common among LBC as a means of attracting their parents' or caregivers' attention and suppressing their loneliness. Su, Li, Lin, Xu, and Zhu (2013) compared LBC with one migrating parent, LBC with two migrating parents, and non-LBC, and found that both groups of LBC experienced a higher degree of loneliness than did non-LBC. In addition, Gao et al (2010) found that, compared to non-LBC, a higher percentage of LBC reported feeling sad or hopeless and had ideations of suicide or leaving home.…”
Section: Emotional and Behavior Problemsmentioning
confidence: 99%
“…Because the individual factors that play a role in this process are not yet clear, researchers have compared only the difference characteristics between LBC and non-LBC. However, parent-child separation refers not only to a single event, but also involves multiple levels of conceptualization, such as the form of the separation (i.e., father migrating, mother migrating, or both parents migrating; Wen & Lin, 2012), the duration of the separation, as well as separation distance and location (González-Ferrer, Baizán, & Beauchemin, 2012), parent-child relationship (Jia & Tian, 2010), and frequency of parental home visits (Su et al, 2013). For example, children with two migrating parents reported a longer separation time and less frequent parental visits compared to children with one migrating parent (Su et al, 2013).…”
Section: Emotional and Behavior Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lacking parental monitoring is also a risk factor of adolescent malfunctioning (Matjasko et al, 2007) and has been cited as a key explanation for higher prevalence of problem behaviors of adolescents in single-parent families in the U.S. (McLanahan and Sandefur, 1994). Supportive evidence also emerged for rural children in China showing protective effects of parental presence against loneliness and beneficial effects of parent–child communication on levels of life and school satisfaction and happiness (Su et al, 2013). …”
Section: Introductionmentioning
confidence: 98%
“…Previous studies have shown that as compared with their non-left-behind peers, left-behind children were more likely to suffer from a high level of loneliness, life dissatisfaction, and unhappiness (Jia and Tian, 2010;Jordan and Graham, 2012;Su et al, 2013). However, there has been a lack of study exploring the influence of parental absence on children's academic performance among the left-behind children.…”
mentioning
confidence: 99%